The effect of Remicade Trough Level on Disease Activity in a Selected Sample of Iraqi Rheumatoid Arthritis Patients - Reem G Hussein; Mohammed Qasim Yahya Malallah A. Al-Atrakji (Iraqi Journal of Pharmaceutical Sciences, 2025)
Rheumatoid arthritis is a lifelong autoimmune arthritic disorder that mostly impacts the small joints, although it can also affect the larger joints. Infliximab is a chimeric monoclonal IgG antibody that specifically targets tumor necrosis factor, a crucial material associated with pathogenic processes. Remicade is an original medication of infliximab. Monitoring the trough level is essential for managing disease activity, while C-reactive protein (CRP) and Erythrocyte Sedimentation Rate (ESR) are utilized to detect inflammation and anticipate the drug’s effectiveness. The study was designed to assess the impact of Remicade trough level on both disease activity and inflammatory biomarkers. A cross-sectional, observational research was carried out at Baghdad Teaching Hospital, involving forty-eight patients who had been diagnosed with rheumatoid arthritis (RA) based on the ACR/EULAR 2010 criteria and were on treatment with Remicade. After 3 months after starting Remicade treatment, measurements were taken for Remicade trough level, CDAI, ESR, and CRP parameters. After a 3-month course of Remicade therapy, the individuals were categorized into four distinct groups based on their CDAI scores (remission, mild, moderate, and severe groups). The trough level of Remicade during remission is 5.6±0.1248µg/mL. In the mild, moderate, and severe groups, the trough levels of Remicade are 4.22±0.1244µg/mL, 2.342±0.1505µg/mL, and 0.72±0.2518µg/mL, respectively. The CDAI score was considerably greater in the severe disease activity group and reduced gradually in the moderate, mild, and remission groups, respectively. The CDAI scores for the severe group are 20.83+-3.219, for the moderate group are 14.77+-0.6218, for the mild group are 5.5+-0.6337, and for the remission, group are 1.34+-0.1086. Furthermore, the findings indicate an inverse correlation between the Remicade trough level and the levels of ESR and CRP. The reduction in the CDAI score, ESR, and CRP was associated with a high level of Remicade in the bloodstream. This also implies that the increase in CDAI score, ESR, and CRP in patients with rheumatoid arthritis may be caused by a drop in the amount of Remicade in the bloodstream.